Molecular evidence of SARS-CoV-2 in New York before the first pandemic wave - Hernandez, Matthew M.; Gonzalez-Reiche, Ana S.; Alshammary, Hala; Fabre, Shelcie; Khan, Zenab; van De Guchte, Adriana; Obla, Ajay; Ellis, Ethan; Sullivan, Mitchell J.; Tan, Jessica; Alburquerque, Bremy; Soto, Juan; et al. (Nature communications, 2021)
Numerous reports document the spread of SARS-CoV-2, but there is limited information on its introduction before the identification of a local case. This may lead to incorrect assumptions when modeling viral origins and transmission. Here, we utilize a sample pooling strategy to screen for previously undetected SARS-CoV-2 in de-identified, respiratory pathogen-negative nasopharyngeal specimens from 3,040 patients across the Mount Sinai Health System in New York. The patients had been previously evaluated for respiratory symptoms or influenza-like illness during the first 10 weeks of 2020. We identify SARS-CoV-2 RNA from specimens collected as early as 25 January 2020, and complete SARS-CoV-2 genome sequences from multiple pools of samples collected between late February and early March, documenting an increase prior to the later surge. Our results provide evidence of sporadic SARS-CoV-2 infections a full month before both the first officially documented case and emergence of New York as a COVID-19 epicenter in March 2020. Matthew M. Hernandez and Ana S. Gonzalez-Reiche and colleagues report evidence of SARSCoV-2 infections in respiratory pathogen-negative nasopharyngeal specimens collected in New York, which date back to over one month before the first officially documented case in the state. The findings provide insights in to the origins of the virus in New York.